Quality of life of higher education students at the Polytechnic Institutes of Santarem and Leiria during the COVID-19 pandemic - Figueiredo, Maria Carmo; Amendoeira, José; Rosa, Marta; Matos, Rui; Silva, Mário; Coelho, Teresa; Gonzaga, Luís; Chicau, Carla (Cuadernos de Psicología del Deporte, 2023)
Objective: This study aims to determine the quality of life of higher education students at the Polytechnic Institutes of Santarem and Leiria during the COVID-19 pandemic. Methods: The population consists of 6483 students attending higher education, from both Institutes. A total of 775 participants selected by convenience sampling, participated in the study. Study with a quantitative, descriptive, correlational character, aiming to describe phenomena and, in addition, identify and explore possible relationships between variables. The WHOQOL-Bref instrument adapted from WHO was applied. The data treatment and analysis were performed using descriptive, correlational and inferential statistics. Results: Students’ self-assessment about Quality of Life is globally superior to the self-assessment with their satisfaction with health, where the female students have lower average values ​​than the male students. The WHOQOL-Bref domains referring to Quality of Life with higher values ​​were the Physical and Environment domain, with the Social Relations and Psychological domains having the lowest values. Conclusion: The results point to the need for intervention to promote the Quality of Life of students, focusing on psychosocial factors, due to the conditions imposed during the confinement period, by the pandemic COVID-19.